Composition of planktonic foraminifera test-bound organic material and implications for carbon cycle reconstructions - Paoloni, Tommaso; Hoogakker, Babette; Navarro Rodriguez, Alba; Pereira, Ryan; McClymont, Erin L.; Jovane, Luigi; Magill, Clayton (Frontiers in Marine Science, 2023)
Foraminiferal shells are extensively used to reconstruct the marine environment in the geological past. The foraminifera test-bound organic material (FBOM), sheltered by the test from potential diagenetic alteration and contamination, has great feasibility to improve our understanding of carbon and nitrogen cycling. The FBOM δ 13 C was proposed as a proxy for reconstructing past environmental conditions. However, to fully exploit the proxy potential of FBOM, its molecular composition and the influence of the latter on the FBOM δ 13 C need to be assessed. Here we use a novel combination of gas chromatography-mass spectrometry, flame ionization detection (GC-MS/FID) and liquid chromatography organic carbon and nitrogen detection (LC-OCD/OND) analyses to study the FBOM chemical composition. Our results indicate that polysaccharides and proteins dominate FBOM, as proposed by earlier studies, with no evidence of detectable lipids (alkyl lipids, trimethylsilyl ethers of fatty alcohols, trimethylsilyl esters of fatty acids and steranes derivatives were targeted). Previous studies suggested that FBOM δ 13 C may be used to reconstruct past atmospheric CO2 concentrations. However, our results indicate that the use of FBOM δ 13 C to reconstruct CO2 carries an approximate uncertainty of ±21 ppm for past atmospheric CO2 abundance. We suggest that FBOM δ 13 C can be used as a novel proxy to reconstruct particulate organic material (POM) δ 13 C. This is also supported by the recently confirmed minor fractionation between POM and FBOM δ 13 C. Keywords: Organic matter, planktonic foraminifera, gas chromatography, liquid chromatography, lipids, particulate organic matter proxy.1. INTRODUCTION The calcite making up foraminifera hard shells (called the 'test') has been extensively used to study biogeochemical cycling in the oceans. The carbon isotopic composition of foraminifera calcite tests (δ 13 C) has been widely applied to infer changes in carbon cycling between the oceans and land/ atmosphere reservoirs, as well as ocean circulation (Duplessy et al., 1984;Mackensen and Bickert,